2006
DOI: 10.1029/2006gl027064
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of peak electron density in upper ionosphere of Mars at high latitude (50°–70°N) using MGS ACC data

Abstract: Under photochemical equilibrium condition, electron density near peak varies as the square root of total peak ionization rate. Thus by averaging the longitudinal variation of latter, the mean primary and secondary peak electron densities in upper ionosphere of Mars using measured mass densities at LST 16 hrs are estimated to be ∼8.56 × 104 cm−3 and ∼1.81 × 104 cm−3. On comparison with mean electron densities at LST 3–4 hrs for observational period Dec. 24–31, 1998, at same solar zenith angle, it is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…A wave 3, as seen by Bougher et al in the peak heights of the E and F layers, was also found in the neutral scale height. Similar analysis by Haider et al [2006] and Seth et al [2006a, 2006b] confirmed the presence of wave 3 in the Mars ionosphere. Wang and Nielsen [2002] provided evidence of topographic effects in the Martian ionosphere by analyzing the earlier Mariner 9 occultation data.…”
Section: Ionospheric Measurements On Marssupporting
confidence: 70%
See 1 more Smart Citation
“…A wave 3, as seen by Bougher et al in the peak heights of the E and F layers, was also found in the neutral scale height. Similar analysis by Haider et al [2006] and Seth et al [2006a, 2006b] confirmed the presence of wave 3 in the Mars ionosphere. Wang and Nielsen [2002] provided evidence of topographic effects in the Martian ionosphere by analyzing the earlier Mariner 9 occultation data.…”
Section: Ionospheric Measurements On Marssupporting
confidence: 70%
“…MGS accelerometer data of mass density variation with longitudes for the latitude range 50–70°N from altitudes 130 and 160 km with experimental error bars. Solid curve indicates the best fit to data and dotted curves represent 0.95 prediction confidence limits [from Seth et al , 2006b]. The propagating mode 3 of atmospheric tide is found to be the dominant cause of this perturbation.…”
Section: Mars' Neutral Atmospherementioning
confidence: 99%
“…where I(∞, l) is the emissivity, T is the temperature, Ne is the electron density of the coronal plasma, h is Planck's constant, k is Boltzmann constant, c is the velocity of light, m is the mass of electron, e is electronic charge, G is total Gaunt factor representing the continuum emission, s i A (l) and s i I (j,l) are respectively the photoabsorption and photoionization cross sections to the jth ion state of the constituent i at wavelength l, ch(l) is a generalized Chapman function [Seth et al, 2006a[Seth et al, , 2006b, d(hc/l À E o À W ji ) is the delta function in which hc/l is the incident photon energy, W ji is the ionization potential of jth ion state of ith constituent and E o is the energy of ejected electron.…”
Section: Ays Methodsmentioning
confidence: 99%
“…Thus the vertical transport of photoelectrons is inhibited. The photoelectron impact ionization rates are calculated as given below: where J(h, χ ) is the photoelectron impact ionization rate at altitude h and solar zenith angle χ , the primary photoelectron spectrum R i (h, χ ,E) is calculated by Seth et al [2006a, 2006b] at solar zenith angle 77 degree using generalized Chapman function as given by Smith and Smith [1972], the photoionization rate R i (h, χ ) is obtained from primary photoelectron spectrum R i (h, χ ,E) by integrating it over energy E, i represents ith gas, E o is incident energy of monoenergetic electrons, which were introduced in a gas medium, E is the energy of secondary or tertiary electrons, which are calculated at that time when primary electrons ionize the atmospheric gases, and U c (E,E o ) is two dimensional composite yield spectrum at energy E o and E. The composite yield spectrum approach is obtained by weighting the component of yield spectrum U(E,E o ) as given below: In this equation C 0 , C 1 and C 2 are adjustable parameters of different gases, which are given by Singhal and Green [1981]. The value f i is the fractional composition and is given by where S i /S j is the average value of σ Ti (E)/ σ Tj (E) between E min = 2 eV to E o , is the total (elastic and inelastic) cross sections, which are taken from Porter and Jump [1978] and Jackman et al [1977] and n i (h) is the neutral density.…”
Section: Methodsmentioning
confidence: 99%